2020
DOI: 10.33087/legalitas.v12i2.223
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Majelis Pengawas Notaris Daerah terhadap Pelaksanaan Kode Etik Notaris di Kabupaten Serang

Abstract: The role of the Supervisory Council is very important in fostering and supervising the position of a Notary on an ongoing basis regarding personal behavior in carrying out his position and outside his position as the spearhead of ensuring legal certainty for the public who uses the services of a Notary. Enforcement of the Code of Ethics for the Notary profession is one way to preserve noble values in the Notary profession, so that this noble profession in its implementation will not experience a decrease in qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Other research is like that conducted by (Hasuri et al, 2020) which found that the specific goals that are expected to be achieved through the service program in boarding school are improving the quality of education and personality of Pesantren students and creating discipline within the pesantren environment so as to create effective and efficient patterns of communication and handling of deviant behavior. There is also research from (Majid, 2022) which finds that the law clearly regulates provisions relating to violence against children.…”
Section: Introductionmentioning
confidence: 99%
“…Other research is like that conducted by (Hasuri et al, 2020) which found that the specific goals that are expected to be achieved through the service program in boarding school are improving the quality of education and personality of Pesantren students and creating discipline within the pesantren environment so as to create effective and efficient patterns of communication and handling of deviant behavior. There is also research from (Majid, 2022) which finds that the law clearly regulates provisions relating to violence against children.…”
Section: Introductionmentioning
confidence: 99%
“…Peran kode etik disini merupakan cara untuk melestarika nilai dalam pelaksaan jabatannya (Hasuri, Rokilah, & Pitasari, 2020). Sedangkan penelitian yang dilakukan oleh Irma Mulia Ftri, Ilyas Ismail dan Suhaimi pada tahun 2019 dalam menemukan bahwa pengawasan terhadap Notaris dilakukan oleh Menteri.…”
unclassified